Reducing gas pressure pulsations in the suction line of a piston compressor when using throttle washers - S. S. Busarov; A. A. Kapelyukhovskaya; V. V. Voronin; K. A. Bakulin; N. G. Sinitsin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article discusses the problem of combating pressure fluctuations in the suction line of piston compressors. As you know, incorrect calculation of communications can lead to accidents of compressor equipment. Therefore, special attention must be paid to the layout of pipelines and equipment, while avoiding resonance phenomena. One way to combat pressure pulsations in the suction line is to install diaphragms. This method is the cheapest and easiest to implement, especially for compressors already in operation. The experimental studies carried out confirmed the known data that the area of the diaphragm opening should be four times smaller than the diameter of the pipeline. At the same time, a threefold reduction in the amplitude of pressure fluctuations is achieved. Installation of a diaphragm design with parameters close to the recommended ones is possible anywhere in the suction line, since the change in amplitude at different pressure from the suction valves does not exceed 5...7 %. When installing a diaphragm with dimensions different from those recommended, it is necessary to install it closer to the suction valve.